Allergic sensitization is associated with inadequate antioxidant responses in mice and men. Issue 10 (6th August 2015) - Utsch, L.; Folisi, C.; Akkerdaas, J. H.; Logiantara, A.; van de Pol, M. A.; van der Zee, J. S.; Krop, E. J. M.; Lutter, R.; van Ree, R.; van Rijt, L. S.
Abstract Background Allergies arise from aberrant Th2 responses to allergens. The processes involved in the genesis of allergic sensitization remain elusive. Some allergens such as derived from house dust mites have proteolytic activity which can induce oxidative stress in vivo. A reduced capacity of the host to control oxidative stress might prime for allergic sensitization. Methods Two different strains of mice were compared for their antioxidant and immune response to HDM. Protease activity of the HDM extract was reduced to investigate its role in oxidative stress induction in the airways and whether this induction could determine allergic sensitization and inflammation. The role of oxidative stress in allergic sensitization was also investigated in humans. An occupational cohort of animal workers was followed for the development of sensitization to rodent urinary proteins. Levels of oxidative stress in serum and antioxidant responses by PBMCs were determined. Results Susceptibility to allergic sensitization to mite allergens in mice was highly dependent on host genetic background and was associated with oxidative stress in the lungs before allergen exposure and poor antioxidant response after allergen exposure. Reduction in mite protease activity limited its capacity to induce oxidative stress and allergic inflammation in mice. We showed that also in human subjects, oxidative stress before allergen exposure and poor antioxidant responses were associated with predisposition to occupational allergy. Conclusion Our study indicates that oxidative stress condition before allergen exposure due to an inadequate antioxidant response may prime for allergic Th2 responses.